Posterior reversible encephalopathy and status epilepticus in Takayasu arteritis - Kumar, Munish; Anand, Vishal; Nadeem, Rashid (International Journal of Research in Medical Sciences, 2021)
Takayasu arteritis (TA) is a rare, systemic, chronic inflammatory condition causing granulomatous vasculitis of medium-sized and large arteries of unknown etiology. A possible relationship between Takayasu arteritis and tuberculosis has been suggested but not proven until now. Posterior Reversible Encephalopathy Syndrome (PRES) and seizure are rare complications. We report a case of Takayasu arteritis with lymph node tuberculosis presented with status epilepticus and Posterior reversible encephalopathy syndrome.